Ratiometric fluorescence measurements of membrane potential generated by yeast plasma membrane H(+)-ATPase reconstituted into vesicles - Holoubek, A; Vecer, J; Opekarová, M; Sigler, K (Biochimica et biophysica acta, 2003)
Potential-sensitive fluorescent probes oxonol V and oxonol VI were employed for monitoring membrane potential (Delta(psi)) generated by the Schizosaccharomyces pombe plasma membrane H(+)-ATPase reconstituted into vesicles. Oxonol VI was used for quantitative measurements of the Delta(psi) because its response to membrane potential changes can be easily calibrated, which is not possible with oxonol V. However, oxonol V has a superior sensitivity to Delta(psi) at very low concentration of reconstituted vesicles, and thus it is useful for testing quality of the reconstitution. Oxonol VI was found to be a good emission-ratiometric probe. We have shown that the reconstituted H(+)-ATPase generates Delta(psi) of about 160 mV on the vesicle membrane. The generated Delta(psi) was stable at least over tens of minutes. An influence of the H(+) membrane permeability on the Delta(psi) buildup was demonstrated by manipulating the H(+) permeability with the protonophore CCCP. Ratiometric measurements with oxonol VI thus offer a promising tool for studying processes accompanying the yeast plasma membrane H(+)-ATPase-mediated Delta(psi) buildup.
Keywords: buněčná membrána; fluorescenční barviva; Saccharomyces cerevisiae; Spectrometry, Fluorescence; membránové potenciály; fluorescenční spektrometrie; Fluorescent Dyes; Membrane Potentials; Proton-Translocating ATPases; protonové ATPasy; Cell Membrane